Auditing theory : a guide in understanding Philippine standards on auditing - Salosagcol, Jekell G.; Tiu, Michael ;Hermosilla, Roel (Espana Manila, Philippines : CRC-Ace Review School, 2018)
In recognition of the limited number of units made available for the study of auditing theory, every effort has been made to keep this book concise and to the point, while providing faithful representation of auditing standards and principles.
Chapter 1. AUDIT - An Overview -- Chapter 2. The professional standards -- Chapter 3. The Auditor's responsibility -- Chapter 4. The audit process-accepting an engagement -- Chapter 5. Audit Planning -- Chapter 6. Consideration of internal control -- Chapter 7. Auditing in a computerized environment -- Chapter 8. Performing Substantive Tests -- Chapter 9. Audit SSampling -- Chapter 10. Completing the audit -- Chapter 11. Audit Reposts on Financial statements -- Chapter 12. Assurance and related services -- Chapter 13. The code of ethics and Republic Act 9298.
Keywords: AUDITING